2020
DOI: 10.1080/09658211.2020.1727521
|View full text |Cite
|
Sign up to set email alerts
|

Effects of collaboration on the qualities of autobiographical recall in strangers, friends, and siblings: both remembering partner and communication processes matter

Abstract: Recalling autobiographical memories with others can influence the quality of recall, but little is known about how features of the group influence memory outcomes. In two studies, we examined how the products and processes of autobiographical recall depend on individual vs. collaborative remembering and the relationship between group members. In both studies, dyads of strangers, friends, and siblings recalled autobiographical events individually (elicitation), then either collaboratively or individually (recal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 59 publications
(111 reference statements)
0
5
0
Order By: Relevance
“…The amplitude of collaborative inhibition is operationally defined as the amount of correctly retrieved information by nominal groups minus that retrieved by collaborative groups. This value varies from one circumstance to another, and it has been affected by (a) collaborative participant relationships (Grysman et al, 2020;Harris et al, 2017Harris et al, , 2018Selwood et al, 2020), (b) member size of the collaborative group (see Marion & Thorley, 2016 for a review), and (c) other factors (see below paragraphs for information). For instance, Harris et al (2017Harris et al ( , 2018 found that the members of collaborative groups comprised of strangers might apply distinct retrieval strategies that exacerbate the amplitude of collaborative inhibition, while the members of groups comprised of acquaintances (e.g., friends) or intimate partners (e.g., married couples) might hold a transactive memory system that encourages them to adopt similar cognitive organizations that tend to attenuate the amplitude of collaborative inhibition.…”
Section: Other Factors Influencing Collaborative Memory -Emotional Va...mentioning
confidence: 99%
“…The amplitude of collaborative inhibition is operationally defined as the amount of correctly retrieved information by nominal groups minus that retrieved by collaborative groups. This value varies from one circumstance to another, and it has been affected by (a) collaborative participant relationships (Grysman et al, 2020;Harris et al, 2017Harris et al, , 2018Selwood et al, 2020), (b) member size of the collaborative group (see Marion & Thorley, 2016 for a review), and (c) other factors (see below paragraphs for information). For instance, Harris et al (2017Harris et al ( , 2018 found that the members of collaborative groups comprised of strangers might apply distinct retrieval strategies that exacerbate the amplitude of collaborative inhibition, while the members of groups comprised of acquaintances (e.g., friends) or intimate partners (e.g., married couples) might hold a transactive memory system that encourages them to adopt similar cognitive organizations that tend to attenuate the amplitude of collaborative inhibition.…”
Section: Other Factors Influencing Collaborative Memory -Emotional Va...mentioning
confidence: 99%
“…Typically, in such studies, participants co-operate to recall information that they obtained previously, either individually or as part of a pair or larger group. These pairs or groups can consist of strangers (Andersson & Rönnberg, 1995Bärthel et al, 2017;Browning et al, 2019;Selwood et al, 2020;Vredeveldt et al, 2019), friends (Andersson & Ronnberg, 1997;Andersson & Rönnberg, 1995Selwood et al, 2020;Vredeveldt et al, 2019), siblings (Selwood et al, 2020) or romantic partners (Barnier et al, 2018;Browning et al, 2019;Harris et al, 2011;Johansson et al, 2005).…”
Section: Collaborative Recallmentioning
confidence: 99%
“…Typically, in such studies, participants cooperate to recall information that they obtained previously, either individually or as part of a pair or larger group. These pairs or groups can consist of strangers [ 38 43 ], friends [ 38 , 39 , 42 44 ], siblings [ 42 ] or romantic partners [ 41 , 45 47 ]. The information to be recalled differs, and study materials range from a list of words without personal relevance [ 44 , 46 , 47 ], actions within a computerized memory task [ 41 ], video materials [ 38 , 40 , 43 ], a list with items of personal relevance [ 46 ], stories [ 38 , 47 ] and autobiographical interviews [ 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…To cite another example, foundational questions in philosophy of mind involve the relationships between memory, self-knowledge, and group minds. Recent research suggests that combining conceptual and experimental research methods on autobiographical recall clarifies the ways that collaborative processes impact the quality of certain memories (Selwood et al, 2020). It is reasonable to suppose that grounding research in strong conceptual frameworks as well as experimental reforms motivated by crisis science may increase the reliability of research.…”
Section: Proposals For Reliable Philosophical Researchmentioning
confidence: 99%